1973
DOI: 10.1159/000208383
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Normal Haemopoiesis in Rats during the Development of Acute Leukaemia

Abstract: The reaction of normal haemopoiesis under the development of a transferable acute leukaemia was studied in the rat. A reduction of cell numbers was observed in the bone marrow in the proliferating compartments of erythropoiesis, megakaryocytopoiesis and myelopoiesis. In the peripheral blood, erythrocyte and platelet levels decreased to one tenth of normal: Granulocytes and lymphocytes showed an increase coincident with the increase in circulating leukaemic cells before a final tendency to decline. These change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Ph‐positive stem cells are, however, assumed to be resistant to this feedback regulation. This assumption is consistent with studies of the growth of CML progenitor cells in cultures and is also consistent with the results of studies of leukemia in animal models [18].…”
Section: Methodssupporting
confidence: 91%
“…Ph‐positive stem cells are, however, assumed to be resistant to this feedback regulation. This assumption is consistent with studies of the growth of CML progenitor cells in cultures and is also consistent with the results of studies of leukemia in animal models [18].…”
Section: Methodssupporting
confidence: 91%
“…In a group of animals investigated under the same conditions as described here [6] it was found that the number of platelets declined to about one tenth of normal value 6 days after transfusion of LC. The bleeding may be fur ther due to disorders of hemostasis known to develop during the course of this leukemia [7J.…”
Section: Discussionsupporting
confidence: 53%
“…Rats of both sexes from the inbred BD IX strain (Druckrey, 1971) and the acute leukaemia L 5222 (Hoelzer, 1973;Hoelzer et al, 1973) were used. Following a dose of lo7 cells, as used in these experiments, survival time is 6-7 days.…”
Section: A T E R I a L S A N D M E T H O D S Animals And Leukaemiamentioning
confidence: 99%